Spontaneous Resolution of Catheter-Induced Iatrogenic Vein Graft Dissection: First Case Report and Review of Literature - Suryanarayana, Prakash; Kollampare, Shubha; Movahed, Mohammad Reza (International Journal of Angiology, 2016)
An 86-year-old female patient with a history of bypass surgery was admitted for recurrent dyspnea and chest pain on exertion. She underwent coronary angiography showing high-grade saphenous vein graft stenosis supplying the right coronary. During an attempt to perform percutaneous intervention, saphenous vein graft to the right coronary artery was injured by the guide catheter resulting in dissection with thrombus formation but with normal distal blood flow. The procedure was abandoned since she had normal distal flow and also due to a fear of causing extension of the dissection with further manipulation. The patient was hemodynamically stable and free of chest pain after 30 minutes of observation. The patient was later discharged home on medical treatment. After 1 month, a repeat angiography showed patent saphenous vein graft to the right coronary artery with healed dissection. This is the first case report of spontaneous recovery of iatrogenic saphenous vein graft dissection. This case is followed by the review of literature.
Keywords: dissection; saphenous vein graft; angiography; cardiac catheterization; coronary intervention